84.9k views
25 votes
36x^3 +27x^2=0 pls help me solve :/​

User Habit
by
5.1k points

2 Answers

9 votes

Answer: 36x^3 +27x^2 = 9x^2\left(4x+3\right)

Step-by-step explanation: apply exponent rule rewrite factor out common term plz enjoy

User Kurdtc
by
5.5k points
1 vote

Answer:


x = 0\; ,-(3)/(4)

Explanation:


36x^3 + 27x^2 = 0

  • Take 9x² common from the expression on L.H.S.


=> 9x^2(4x + 3) = 0

Here, x will have 2 values :-

1)
9x^2(4x + 3) = 0

  • Divide both the sides by (4x + 3)


=> (9x^2(4x + 3))/((4x+3)) = (0)/(4x+3)


=> 9x^2 = 0

  • Divide both the sides by 9x


=> (9x^2)/(9x) = (0)/(9x)


=> x = 0

2)
9x^2(4x + 3) = 0

  • Divide both the sides by 9x²


=> (9x^2(4x + 3))/(9x^2) = (0)/(9x^2)


=> 4x+3 = 0

  • Substract both the sides from 3


=> 4x+3 -3 = 0 - 3


=> 4x=-3

  • Divide both the sides by 4


=> (4x)/(4) = (-3)/(4)


=> x = -(3)/(4)

User Fabian Jakobs
by
5.3k points